Development of interactive software (Statics) - Teo, Royston Jia Jun (2018)
This report provides a detailed account of the entire progression of the Final Year Project (FYP): C028 Development of Interactive Software (Statics). It aims to be of use for solving static beam problems. The software uses direct stiffness method as the main method to solving all the beam problems. This report comprises of 5 chapters in total, the introduction suggest the importance and applications of statics in real world scenarios followed by a timeline for this project. Next is the research segment which comprises of research done by previous students of the same project, concepts for static analysis and programming methods in the context of solving static problems. Following that, an explanation of the different types of static problems and their categories with examples included. The second half of the report then showcases the interactive software and its operation. The interactive software aims to enhance tedious calculations for different type of static beam analysis configurations. Examples of its application to different static analysis configurations are also included in this segment. Lastly, it ends off with the benefits and limitations of this project.